Clinical Presentation and Anatopathologic Finding of a Hepatic Vascular Hamartoma: a Case Report. - Valentina Ferri; Benedetto Ielpo; Hipolito Duran; Eduardo Diaz; Isabel Fabra; Carlos Plaza; Yolanda Quijano; Emilio Vicente (Annals of Hepatology, 2019)
HVH (hepatic vascular hamartoma) is a tumor like malformation arising from the vascular tissue of the liver. HVH has been previously reported in animals and presents distintive features from the most frequent benign tumor like malformation of the liver, the hepatic mesenchymal hamartoma (HMH). Herein we report a case of HVH localized in hepatic segment 4b, involving the gastro hepatic ligament, successfully treated with total excision. We describe the anatomo-pathologic findings focusing on the clinical and radiological presentation, the intraoperative characteristics and the differential diagnosis.